DESCRIPTION OF KNOWLEDGE ABOUT THE POST PLACENTA IUD (INTRA UTERINE DEVICE) CONTRACEPTIVE METHOD FOR PREGNANT - Laila, Fadliyah; Mardhika, Amellia; Sulfat, Emuliana; Iswatun, Iswatun; Wijayanti, Endah Sri; A. S, Nela (Journal of Vocational Nursing, 2021)
Introduction: Post-placental IUD is a long-term contraceptive method with an effective pregnancy prevention 0.6-0.8 pregnancies / 100 women. Installation that is carried out when the mother gives birth has an impact on the coverage of contraceptive use from an early age. Post-placental IUD contraceptives are not only effective in the long term for up to 10 years but are also affordable contraceptives for people from low to high economies status. Currently, these contraceptives can be purchased or installed for free. Contraception does not interfere with milk production, does not require routine follow-up to the hospital, contraceptive examinations can be done independently. The purpose of this study was to describe the knowledge about the post-placenta IUD contraceptive method. Methods: This study used a descriptive design, with a population of 98 people and a sample of 54 people. The sampling used is purposive sampling. Collecting data with a closed questionnaire. Data processing and data analysis by editing, scoring, coding, tabulating and presented in narrative form then draw conclusions. Results: Based on the results of the study, it was found that most (78.1%) pregnant women had less knowledge about Post Placenta IUD contraception. Conclusion: The reference of this study is to increase knowledge about the Post Placenta IUD (Intra Uterine Device) contraceptive method in pregnant women. Periodic health education regarding this contraceptive method during pregnancy so that at delivery, post placenta IUD contraception can be immediately installed.